2006
DOI: 10.1089/cap.2006.16.336
|View full text |Cite
|
Sign up to set email alerts
|

AOne-Year Open-Label Trial of Risperidone Augmentation in Lithium Nonresponder Youth with Preschool-Onset Bipolar Disorder

Abstract: A substantial proportion of youth with a history of preschool-onset BD treated with lithium were either nonresponders or partial responders. Subsequent augmentation of lithium with risperidone in these cases was well tolerated and efficacious. Potential predictors of lithium nonresponse identified in this study may guide the choice of medications earlier in the treatment process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(42 citation statements)
references
References 63 publications
0
41
0
1
Order By: Relevance
“…51 Divalproex sodium plus risperidone or lithium plus risperidone in 37 patients promoted significant improvement in the YMRS, the CDRS-R, and the CGI-BP (p , 0.001). There were no significant between-group differences in terms of efficacy, safety, or tolerability.…”
Section: **mentioning
confidence: 97%
See 1 more Smart Citation
“…51 Divalproex sodium plus risperidone or lithium plus risperidone in 37 patients promoted significant improvement in the YMRS, the CDRS-R, and the CGI-BP (p , 0.001). There were no significant between-group differences in terms of efficacy, safety, or tolerability.…”
Section: **mentioning
confidence: 97%
“…Data are summarized in Table 2. [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] Case reports and case series were detected, but were not included in the text due to the availability of higher-level evidence for the psychopharmacological agents of interest. Nevertheless, we recommend analysis of these case series and reports, which are available from the authors on request.…”
Section: Randomized Controlled Trials/meta-analysesmentioning
confidence: 99%
“…Open-label (OL) studies, with more homogeneously defined diagnostic criteria, have suggested that children treated with lithium achieve a response rate between 38% and 55% as monotherapy and 82% when used in combination with second-generation antipsychotics (SGAs) (e.g., risperidone) (11)(12)(13). In one OL lithium study of 100 adolescents (12-18 years of age) with an acute manic episode, 63% achieved response and 26% stayed in remission (14).…”
Section: Lithiummentioning
confidence: 99%
“…Metabolic side effects were a concern in the risperidone group. An open-label combination treatment study examined the efficacy of augmenting lithium treatment with risperidone in 38 children aged 4-17 with onset of bipolar disorder in preschool years [59]. There were 21 participants who were considered lithium non-responders after 8 weeks of monotherapy who received risperidone augmentation for up to 11 months.…”
Section: Atypical Antipsychoticsmentioning
confidence: 99%